The digitisation of knowledge produces hybrids: Politics and identities in MOOCs - Perrotta, Carlo (Proceedings of the International Conference on Networked Learning, 2014)
This paper offers a conceptual analysis of Massive Online Open Courses (MOOCs) that draws on Actor Network Theory (ANT). MOOCs are viewed as part of a hybrid collection of events, technologies, networks and interests: an "assemblage" where discourse, materiality and sociality are bound up in each other. The ANT-derived notion of ontological politics is used as a broad framework to discuss the negotiations and performances that confer reality to the MOOC assemblage. In particular, the paper focuses on those features of the MOOC phenomenon that relate to, and stem from, the sociotechnical apparatus of digitisation technology. Digitisation is viewed as a "black box" that seemingly operates as a unity, but in fact is a multifaceted, messy, networked phenomenon in its own right that encompasses a wide range of actors, relationships and practices. Exploring the internal workings of such black box uncovers interesting ramifications and taken-for-granted assumptions that can shed light on the MOOC phenomenon. In particular, the paper argues that digitisation technology is associated with the emergence of a hybrid actant: the DVR (Digital Video Recorder) Teacher. A parallel is drawn between the "interactive affordances" of digital instruction and the playback and cataloguing options that have contributed to massive shifts in TV viewing habits: pause, rewind, fast-forward, download, indexing, collecting, organising, uncommitted viewing. The paper’s chief contention is as follows: the properties of digitisation technology, and the related economic dealings, have contributed to the assimilation of academic instruction into the ontological space of digital TV watching, with its HCI (Human-Computer Interaction) apparatus. Discussing the nature of MOOC attendance, the paper suggests that Digitisation technology (software platforms and algorithms) contributes to the creation of an "entity" (the DVR Teacher) that encapsulates "interactive high quality academic content in a high-production quality presentation". The DVR teacher is further described as an artefact in the service of a neoliberal project of commoditised, pick-and-mix self-improvement, which recruits digitisation to meet a growing demand for "upgrades to the self". Discussing patterns of MOOC attendance, the paper argues that a new breed of "academic content watcher" may be on the rise - one for whom the existential rewards of browsing and tinkering with MOOCs overshadow whatever use value the original, "certifiable" content knowledge may have possessed. In this respect, the real “innovation” of MOOCs lies solely in the offer of (relatively) novel opportunities to enlist the consumption of knowledge for the production of subjectivities.